CALCAREOUS NANNOFOSSIL TAXONOMY AND BIOSTRATIGRAPHY OF THE TOARCIAN-LOWER BAJOCIAN COLLE DI SOGNO SECTION (LOMBARDY BASIN, SOUTHERN ALPS, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Calcareous nannofossil biostratigraphy was conducted in the Toarcian-lower Bajocian interval at Colle di Sogno (Lombardy Basin, Southern Alps, Northern Italy) where the type-section of the Sogno Formation consisting of pelagic marly limestone, marlstone and marly claystone was established. Semiquantitative analyses of calcareous nannofossil assemblages allowed to achieve a high-resolution biostratigraphy based on several biohorizons, including zonal/subzonal markers and additional events. The NJT5 to NJT9 Zones of the standard nannofossil zonation established for the Mediterranean Province were identified. The biostratigraphy obtained at Colle di Sogno was compared to published nannofossil events calibrated with ammonite zones in sections from SE Spain, S France, Portugal and N Algeria. This assessment evidenced some discrepancies in the succession of events of the standard zonation and, furthermore, resulted in the revision of the age of a few datums. Moreover, some new/additional nannofossil biohorizons are proposed as subzonal markers.A morphometric analysis of the genus Watznaueria was conducted to identify diagnostic features for unambiguous species identification. The species W. colacicchii and W. contracta are distinguished on the basis of the coccolith width/central area width ratio, whereas W. britannica britannica is discriminated by the size - as in the original definition of the species - relative to the new subspecies W. britannica minor. The new species W. gaetanii differs from all other Watznaueria taxa by the bridge ultrastructure. In the Toarcian-Aalenian interval a progressive increase in size of Watznaueria specimens is paralleled by the progressive closure of the central area and the modification of the central area structure passing from a cross (W. colacicchii and W. contracta) to a double-button bridge (W. gaetanii) to a single-button bridge (W. britannica). These intrageneric evolutionary innovations accelerated in the Aalenian under stable paleoceanographic conditions and an oligotrophic regime.
Keywords: Calcareous nannofossils; Toarcian – lower Bajocian; biostratigraphy; Watznaueria taxonomy and evolution.